Post-COVID-19 persistent headache: A multicentric 9-months follow-up study of 905 patients. (July 2022) - Garcia-Azorin, David; Layos-Romero, Almudena; Porta-Etessam, Jesús; Membrilla, Javier A; Caronna, Edoardo; Gonzalez-Martinez, Alicia; Mencia, Álvaro Sierra; Segura, Tomás; Gonzalez-García, Nuria; Díaz-de-Terán, Javier; Gallardo, Victor J; Gago-Veiga, Ana Beatriz; et al.
Background: Headache is a frequent symptoms of coronavirus disease 2019 (COVID-19). Its long-term evolution remains unknown. We aim to evaluate the long-term duration of headache in patients that presented headache during the acute phase of COVID-19. Methods: This is a post-hoc multicenter ambisective study including patients from six different third-level hospitals between 1 March and 27 April 2020. Patients completed 9 months of neurological follow-up. Results: We included 905 patients. Their median age was 51 (IQR 45–65), 66.5% were female, and 52.7% had a prior history of primary headache. The median duration of headache was 14 (6–39) days; however, the headache persisted after 3 months in 19.0% (95% CI: 16.5–21.8%) and after 9 months in 16.0% (95% confidence interval: 13.7–18.7%). Headache intensity during the acute phase was associated with a more prolonged duration of headache (Hazard ratio 0.655; 95% confidence interval: 0.582–0.737). Conclusion: The median duration of headache was 2 weeks, but in approximately a fifth of patients it became persistent and followed a chronic daily pattern.